Perception of farmers on the management of fungal diseases of soybeans (Glycine max [L.] Merr.) in Paraguay - Caballero-Mairesse, Gabriela Giuliana (2024)
Introduction. Paraguay is the sixth largest producer and third largest exporter of soybeans (Glycine max [L.] Merr.) in the world and this crop is the most important socio-economic crop in the country. However, its productivity can be adversely affected by diseases caused by phytopathogenic fungi. In addition, phytosanitary information on  soybean cultivation in Paraguay is limited. Objective. To understand farmers’ perceptions of the main soybean diseases and their management. Materials and methods. Between April and May 2022, a questionnaire in Google Forms format with open and closed-ended multiple-choice questions, was applied to 45 soybean producers aged between 30 and 50 years, who cultivate in areas between 200 to 1000 ha in the departments of Alto Paraná, Itapúa, and Caaguazú in Paraguay. Results. Among the respondents, 56% considered Asian soybean rust (Phakopsora pachyrhizi) as the most significant phytosanitary problem associated with soybean cultivation, followed by late-season diseases (LSD) such as brown spot (Septoria glycines) and frogeye leaf spot (Cercospora kikuchii). Respondents indicated taht they use three to four fungicide applications as a disease control measure, with their choice based on the type of product formulation. A majority of respondents noted that both the cost and frequency of applications increased over time. Additionally, 53% mentioned that biological fungicides are a viable alternative for integrated disease management. Conclusion. The responses obtained in this research allowed obtaining the perception of disease management tactics of soybean producers in Paraguay, underscoring the significance of Asian soybean rust and late-season diseases. However, there is a need for further research that can explore all aspects of pathogen management.